El Panorama de la Minería en el Perú. Entrevista a Hernán Torres Alvarez y Sergio Cueva Chauca - Cueva Chauca, Sergio; Hostia Cardeña, Augusto (Pontificia Universidad Católica del Perú, 2015)
In this interview, the authors explain about the importance and current panorama of the mining activity in Peru, that has generated great benefits for this country. Furthermore, they discussed the major internal and external problems facing the mining industry in the country, and the ways in which these problems have been resolved through new laws. Finally, they give importance to the changes occurring in the international panorama, and that affect the internal mining industry of each country.

En la presente entrevista, los autores explican sobre la importancia y el actual panorama de la actividad minera en el Perú, que ha generado grandes beneficios para el país. Asimismo, comentan los principales problemas internos y externos que enfrenta la industria minera en el país, y las formas en que estos se han ido resolviendo a través de nuevas leyes. Finalmente, se da importancia a los cambios que se dan en el panorama internacional y afectan a la industria minera interna de cada país.
The Panorama of Mining in Peru. Interview with Hernán Torres Alvarez and Sergio Cueva Chauca
Keywords: Mining; Peru; Industry; Social Conflicts; Minería; Perú; Industria; Conflictos Sociales; https://purl.org/pe-repo/ocde/ford#5.05.00